Model based group approach (MBGA); an alternative approach for improving the quality of student learning in Universities - Taufik, Taufik; Afdal, Afdal; Fadli, Rima Pratiwi; Ifdil, Ifdil (Universitas Negeri Padang, 2020)
This research is driven by the phenomenon of the poor quality of learning activities of new students in universities. This study tries to investigate the strength through the work of Model-Based Group Approach to enhance the quality of student learning activities. This research is a quasi-experimental research involved 206 students of Universitas Negeri Padang. The instrument used is IAKB (Activation Instrument Learning Activity) and analysis of research data using T-Test. The result from this research shows that there is an improvement of learning activity quality before and after application of the model that is 13.68 to 57.10. This shows a gain of 43.42%. Based on the results of research that has been done can be concluded that the development of this model is useful to improve the quality of student learning activities.